Development of a novel knee contracture mouse model by immobilization using external fixation. (4th March 2022) - Tokuda, Kotaro; Yamanaka, Yoshiaki; Kosugi, Kenji; Nishimura, Haruki; Okada, Yasuaki; Tsukamoto, Manabu; Tajima, Takafumi; Suzuki, Hitoshi; Kawasaki, Makoto; Uchida, Soshi; Nakamura, Eiichiro; Wang, Ke-Yong; et al.
ABSTRACT: Aims: Several studies have used animal models to examine knee joint contracture; however, few reports detail the construction process of a knee joint contracture model in a mouse. The use of mouse models is beneficial, as genetically modified mice can be used to investigate the pathogenesis of joint contracture. Compared to others, mouse models are associated with a lower cost to evaluate therapeutic effects. Here, we describe a novel knee contracture mouse model by immobilization using external fixation. Methods: The knee joints of mice were immobilized by external fixation using a splint and tape. The passive extension range of motion (ROM), histological and immunohistochemical changes, and expression levels of fibrosis-related genes at 2 and 4 weeks were compared between the immobilized (Im group) and non-immobilized (Non-Im group) groups. Results: The extension ROM at 4 weeks was significantly lower in the Im group than in the Non-Im group (p < 0.01). At 2 and 4 weeks, the thickness and area of the joint capsule were significantly greater in the Im group than in the Non-Im group (p < 0.01 in all cases). At 2 weeks, the mRNA expression levels of the fibrosis-related genes, except for the transforming growth factor-β1, and the protein levels of cellular communication network factor 2 and vimentin in the joint capsule were significantly higher in the Im group (p < 0.01 in all cases). Conclusion: This mouse model may serve as a useful tool to investigate the etiology of joint contracture and establish new treatment methods.